Key Generation for Vigenere Ciphering Based on Genetic Algorithm (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Cryptography is a science securing of information. Encryption requires impregnable keys to encrypt or decrypt data these keys should be unpredictable and not easily to break. In this research we use genetic algorithm to generate keys for vigenere cipher. The best key is used to perform encryption. The keys created by genetic algorithm are tested for randomness by using the entropy test. The entropy calculation shows that randomness of key generated based on genetic processing is better than chosen key in the classical vigenere cipher.